بناء مقياس الروح الرياضية لطلبة المرحلة الرابعة كلية التربية البدنية وعلوم الرياضة جامعة الموصل - الطائي, احمد حازم احمد; السعيد, رافع ادريس عبد الغفور (Sulaimani Journal for Humanities, 2018)
Find a target: *Build the sporting spirit of the students scale the fourth stage College of Physical Education and Sport Sciences University of Mosul. *Develop standard levels for students in the fourth stage College of Physical Education and Sport Sciences University of Mosul scale sporting spirit. The researchers used the descriptive survey manner. Be the research community of students from the fourth stage College of Physical Education and Sport Sciences University of Mosul for the academic year (2013 - 2014), included a sample search on the student's (166) students, divided the sample to the construction guestrooms sample (140) students and by ( 84%), were taken from a sample of construction (24) called for a process of stability and (16) called for an open questionnaire (Expeditionary) experience. The sample application of (26) students and (16%). Use the spirit of sportsmanship, prepared by researchers as a tool for data collection scale, as well as the following tools (questionnaire, interview, build a measurement tool) has included the construction procedures: determining the scale dimensions (after respecting the customs and traditions and social norms, having respect for the opponent, having respect for the laws and regulations of competition, after the approach towards sports participation, after the acceptance and cooperation with others), determine the method of drafting the paragraphs of the scale, the drafting of the paragraphs of each after the initial its image, as well as the adoption of steps and scientific procedures in the construction of the scale and contained virtual honesty of the scale and certified content and sincerity of the construction of (statistical analysis of the vertebrae) my style groups Almtdhad internal consistency, it was used retail midterm stability way and limited statistical methods to: the arithmetic mean and standard deviation equation torsion coefficient (Karl Pearson) and the coefficient of simple correlation for (Pearson) and formula Spearman Brown and t-test and the percentage using automated computer system Spss. I found the following: -Build sportsmanship scale for students of the fourth stage College of Physical Education and Sport Sciences University of Mosul. -Was reached standard levels for the research sample scale sporting spirit.